2004
DOI: 10.1021/bm049574c
|View full text |Cite
|
Sign up to set email alerts
|

Refilling of Ocular Lens Capsule with Copolymeric Hydrogel Containing Reversible Disulfide

Abstract: Polymer solutions can fill any potential irregular cavity using minimally invasive techniques and thus have potential uses in ophthalmology. We prepared acrylamide hydrogels containing disulfide bonds by free radical polymerization in aqueous ethanol. The hydrogels were liquefied using dithiothreitol to yield water-soluble acrylamide copolymers containing pendant thiol (-SH) groups. The weight average molecular weights of the copolymers ranged from 1.43 x 10(5) to 9.22 x 10(5) daltons by GPC. Ellman's analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 39 publications
2
91
0
Order By: Relevance
“…Ravi et al 22 reported on an injectable hydrogel prepared by oxidation of an aqueous solution of acrylamide copolymers containing pendant thiol (−SH) groups. Gelation was achieved through a thiol-disulfide exchange reaction by adding 3,3′-dithiodipropionic acid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ravi et al 22 reported on an injectable hydrogel prepared by oxidation of an aqueous solution of acrylamide copolymers containing pendant thiol (−SH) groups. Gelation was achieved through a thiol-disulfide exchange reaction by adding 3,3′-dithiodipropionic acid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many examples in the literature place the accent on the conjugate addition of thiol groups to unsaturated groups such as acrylic and vinyl sulfone, for the production of hydrogels, by using both bi-or multifunctional thiolbearing molecules. [24] Among the reagents used for this purpose, trimethylolpropane tris(3-mercaptopropionate) (TT) shows interesting properties in terms of reactivity and the physicochemical features of the final product after addition of its thiol moieties to p systems. [18,[25][26][27][28] In this work, we report the synthesis of new biocompatible, stimulus sensitive and biodegradable hydrogels, obtained by derivatizing inulin (INU) with divinyl sulfone (DV) and succinic anhydride (SA), then by crosslinking the resulting INUDVSA derivative with TT.…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION Hydrogels, consisting of crosslinked hydrophilic polymers, are a large group of materials widely used for biomedical purpose, 1 such as cell encapsulation, 2,3 contact lens materials, 4,5 wound dressings, 6 drug delivery vehicles 7,8 and artificial organs, 9 for their good biocompatibility and tissue-like elasticity. In addition, hydrogels have high permeability for oxygen, nutrients, and other water-soluble metabolites.…”
mentioning
confidence: 99%